From courtyard to atrium: spatial differentiation in the spontaneous evolution of vernacular architecture and its response to geo-climate - Fan Peng; Feng Xu; Baohua Wen; Xin Gong; Jin Zhou; Ying Yang (Journal of Asian Architecture and Building Engineering)
Vernacular architecture is deeply rooted in specific regions and evolves under urbanization while maintaining a close connection to the natural environment. Using the case study of vernacular courtyards evolving into vernacular atriums, this study examines the spatial distribution characteristics of vernacular atriums in 37 counties (districts) in southern Hebei, China, by mining data through deep learning networks. The results reveal a tendency for vernacular atriums to concentrate in the southwest, while regions less frequented, such as the east and north, hold potential for promotion. Furthermore, the correlation between 15 geo-climatic factors and vernacular atriums is explored. Geodetector analysis indicates that altitude, slope, rainfall, wind speed, sunshine duration, shortwave radiation intensity and PM2.5 provide varying levels of explanatory power for different types of vernacular atriums. The response of different factors reflects the similarities and differences in the needs of various vernacular atriums to improve the living environment and adapt to the climate conditions, such as insulation, sunshade, lighting, rain protection, and ventilation, while adapting the geographical environment through house form and culture. With AI-assisted fieldwork, this study offers insights into the macro-scale climate adaptability of vernacular courtyards, inspiring sustainable development in vernacular architecture.